MINTAQAVIY INNOVATSION INFRATUZILMANING IQTISODIY RIVOJLANISHGA TAʼSIRINI BAHOLASH MEXANIZMLARI (Marketing Journal, 2026)
AbstractThe study identified mechanisms for evaluating the impact of regional innovationinfrastructure on economic development. An integral RII index was developed,covering research environment, financial mechanisms, technology parks, digitalinfrastructure, and human capital. The indicators were standardized using the min–max  normalization method, and weight coefficients were determined based on expertassessment. Panel data regression analysis was applied to evaluate the relationshipbetween the index and economic growth indicators. The empirical analysis wasconducted using regional statistical data of Uzbekistan. The results revealed significantdifferences in the level of innovation infrastructure development across regions. Theproposed methodology served as a practical tool for monitoring regional innovationperformance and supporting evidence-based investment and management decisions.Keywords: regional innovation infrastructure, RII index, economic development,panel data, Uzbekistan.